Occupational therapy in the gynecology infirmary: an approach in the quality of life during hospitalization - Yuriko Obana, Andréia; Oshiro, Milena; Mariani Neto, Coríntio; Ferrari, Solimar (O Mundo da Saúde, 2006)
By means of a case story, this article presents the performance of the occupational therapist in the gynecology infirmary of Maternity Hospital Leonor Mendes de Barros, reference in the East Zone of São Paulo. It describes clinical assistance and it presents the theoretical assumptions that guide the intervention.